Sensitivity to ether anesthesia and to -rays in mutagen-sensitive strains of Drosophila melanogaster. - Gamo, S.; Megumi, T.; Nakashima-Tanaka, E. (Mutation Research, 1990)
An ether-resistant strain of Drosophila melanogaster, Eth-29, has previously been found to be radiosensitive. Some mutagen-sensitive strains are known to be hypersensitive to X-rays in larvae. The correlation between sensitivities to ether anesthesia and to gamma-rays was examined in adult flies of 12 mutagen-sensitive strains and 6 control strains. A wide variation in sensitivities to ether anesthesia, gamma-ray knock-down and gamma-ray lethality was demonstrated. No correlation between DNA-repair capacity and ether sensitivity or gamma-ray knock-down sensitivity was shown. Only mei-9 and mus201, which are deficient in excision repair, as well as Eth-29 were found to be sensitive to gamma-ray lethality. These findings indicate that the targets for ether anesthesia, knock-down and lethality may be different. Lethality appears to be caused by DNA damage, while the other 2 endpoints appear not to be related to DNA damage.